Mental health and gambling in urban female adolescents - Martins, Silvia S. (2007)
This study explores differences in mental health and behavioral disturbances between female gamblers versus nongamblers from a community sample of 232 female urban youth. Female adolescent recreational gambling was associated with high levels of childhood hyperactivity measured at age 6, past-year substance use, and past-year anxiety symptoms.